Determinants of teacher performance: Assessing the influence of training and mentoring in top tiers’ vocational schools - Ali, Nur Berlian Venus; Hanafi, Ivan; Karnati, Neti (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of training and mentoring on teacher performance in SMK PK vocational schools. Using a sequential explanatory mixed-method approach, the research was conducted in two phases: quantitative and qualitative. The study involved 1,110 teachers from 222 vocational schools across West Java Province. Quantitative data were gathered through structured questionnaires and analyzed using PLS-SEM, while qualitative insights were obtained through interviews and document analysis using thematic analysis. The findings reveal that (1) training has a direct positive effect on teacher performance; (2) mentoring has a direct positive effect on teacher performance; (3) training has a direct positive effect on mentoring implementation; (4) training has an indirect positive effect on teacher performance through mentoring; and (5) training and mentoring simultaneously contribute positively to improving teacher performance in SMK PK. Practically, the results underscore the importance for policymakers and school leaders to design integrated professional development programs that combine both elements to foster sustained teacher growth and educational outcomes.